Vulnerabilidad y resiliencia en la España vaciada - Cortés-Ruiz, María; Ibar-Alonso, Raquel (Revista Electrónica de Comunicaciones y Trabajos de ASEPUMA, 2021)
The depopulation of rural areas for the benefit of urban areas is a problem that has been brewing for some decades and that it is not possible to solve with general policies for all areas due to their heterogeneity. As a consequence of this problem, terms such as "Empty Spain" or "Depopulated Spain" have emerged, which refers to areas of Spain with a population density much lower than the rest of the country. Areas like Soria, Zamora, Teruel or León are the places that suffer the most from this problem and their inhabitants have organized themselves into movements that try to highlight the sociodemographic problems that they suffer along with the problems of infrastructure and services. However, not all areas have the same problem, but we find 5 areas with different problems whose study is necessary to do it individually. The objective of this work is to identify geographic groupings that encompass similar needs, despite geographic distance, and to identify the different types of vulnerabilities that exist in Spain. The conclusion of the research is that it is possible to create 5 unique lines of action that encompass all the areas of Empty Spain, adapted to the needs detected in each of the groups.